2023
DOI: 10.3390/antiox12040810
|View full text |Cite
|
Sign up to set email alerts
|

Improving Blueberry Fruit Nutritional Quality through Physiological and Genetic Interventions: A Review of Current Research and Future Directions

Abstract: Blueberry, hailed as an antioxidant superfood, is the fruit of small shrubs in the genus Vaccinium (family Ericaceae). The fruits are a rich source of vitamins, minerals and antioxidants such as flavonoids and phenolic acids. The antioxidative and anti-inflammatory activities derived from the polyphenolic compounds, particularly from the abundantly present anthocyanin pigment, have been highlighted as the major contributing factor to the health-benefitting properties of blueberry. In recent years, blueberry cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 166 publications
0
11
0
Order By: Relevance
“…The potential benefits of photo-selective protective covers and shade nets in terms of light regulation are neverthe-less manifold and include the creation and modification of interior microclimates affecting various growth-related parameters such as canopy temperature, relative humidity, and soil temperature and light (Bastías & Corelli-Grappadelli, 2012;Iglesias & Alegre, 2006;Kalcsits et al, 2017;Krishna et al, 2023;Narjesi et al, 2023;Pallotti et al, 2023). It is through a combination of interconnected, light-related factors that key physiological processes, such as photosynthesis, photomorphogenesis, and stomatal movement are regulated.…”
Section: Benefits Of Photo-selective Protective Covers and Shade Netsmentioning
confidence: 99%
See 3 more Smart Citations
“…The potential benefits of photo-selective protective covers and shade nets in terms of light regulation are neverthe-less manifold and include the creation and modification of interior microclimates affecting various growth-related parameters such as canopy temperature, relative humidity, and soil temperature and light (Bastías & Corelli-Grappadelli, 2012;Iglesias & Alegre, 2006;Kalcsits et al, 2017;Krishna et al, 2023;Narjesi et al, 2023;Pallotti et al, 2023). It is through a combination of interconnected, light-related factors that key physiological processes, such as photosynthesis, photomorphogenesis, and stomatal movement are regulated.…”
Section: Benefits Of Photo-selective Protective Covers and Shade Netsmentioning
confidence: 99%
“…It is through a combination of interconnected, light-related factors that key physiological processes, such as photosynthesis, photomorphogenesis, and stomatal movement are regulated. It has been noted that even conventional "clear" polymer covers of the forms widely used in polytunnels and greenhouses and shade cloths can reduce the total radiant density radiant flux density and PAR by between 30% and 40% (Krishna et al, 2023). Research has also shown that even relatively low-level changes to light transmission can be beneficial or detrimental to plant growth.…”
Section: Benefits Of Photo-selective Protective Covers and Shade Netsmentioning
confidence: 99%
See 2 more Smart Citations
“…As people pay increasing attention to their health, the demand for blueberry fruits is also rising. Consequently, the commercial cultivation areas for blueberry fruits are expanding [1].…”
Section: Introductionmentioning
confidence: 99%